Decision-Making and Informal Political Institutions in Chilean Sub-National Public Investment - Espinoza-Espinoza, V (Springer New York LLC, 2019)
Literature on informal political institutions has focused on the national level, disregarding sub-national contexts where one can expect increased informality. This article analyzes locally allocated Chilean public investment to understand how informal institutions affect regional development and local democracy. Based on 59 interviews with key stakeholders and national authorities, this research analyses the flow of the decision-making process on funds for regional investment. The results show that local bureaucrats introduce innovations to cope with the weaknesses of formal decision-making regulations, and that these may become informal institutions that complement or accommodate the process to obtain the outcomes expected under the formal rule. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.